Sacrul și profanul în modernitatea occidentală. Ocultism, vrăjitorie și mode culturale - Dragoș DRAGOMAN (Eon)
The survival of traditional religious and cultural elements, even in the most degraded forms, tells the story of their capacity to adapt to modern cultural contexts. Moreover, it unravels the ongoing quest for a sense of being in our modern world. On the one hand, the symbolic forms that populated the universe of the tradition still survive, although their form of manifestation are today hardly recognizable. This is the outcome of an enormous process of acculturation, jointly put in place by the Roman Catholic Church and the modern bureaucratic state. Breaking down both religious superstition and the opposition to political centralization managed to offer a new image of the world, that of the absolute sovereign in Heaven and on earth. The joint collapse of the religious faith and of the supreme monarch left the room for a desecrated, hostile and absurd universe, with no sense for living. That is why new tendencies gained ground especially among young Westerners. The current interest for the occult, magic, witchcraft, astrology, Zen, and other cultural fashions is a sign for their need for a new authentic sense of being.